Sertifikasi Elsimil Bagi Calon Pengantin Sebagai Salah Satu Syarat Administrasi Pernikahan Ditinjau Dari Maṣlaḥah Mursalah - Son Haji Saputra; Seno Aris Sasmito (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The elsimil certification programme (siap nikah dan siap hamil) is an electronic application-based nutrition screening programme and premarital health assistance for prospective brides and grooms which is intended as an effort to help plan the formation of a healthy, quality family, ready for marriage and especially ready for pregnancy. The purpose of this study is to determine the implementation of elsimil certification for prospective brides as one of the requirements for marriage administration in Ngawi District, Ngawi Regency in 2023 with a review of maṣlaḥah mursalah. The research method used is qualitative field method, with data collection techniques including interviews, observation, and documentation. The results showed that the implementation of elsimil certification in Ngawi District, Ngawi Regency, is not fixed on the rules that require 3 months of assistance before marriage, because for those whose marriage registration is too tight, elsimil certification assistance can be proposed after marriage. So, the bride-to-be can still get married according to the planned time and certainly does not complicate the marriage. The benefit contained in the elsimil certification is ḥājiyyāt because it can avoid difficulties in the framework of ḥifẓu an-nasl.